HEMATOLOGICAL VALUE OF TOTAL ERYTHROCYTES AND HEMOGLOBIN LEVEL OF BALI CATTLE WITH ORGANIC FORAGE FEED - Septiarini, Anak Agung Ananda; Suwiti, Ni Ketut; Suartini, I Gusti Ayu Agung (Buletin Veteriner Udayana, 2020)
Organic forage has become the choice of bali cattle feed in Bali, so it is necessary to know its effect on the total erythrocytes average and hemoglobin levels of bali cattle. This study used ten samples of bali cattle aged 12-18 months. Blood samples were taken through the jugular vein using venoject. Total erythrocyte examination and hemoglobin levels of bali cattle were measured using a Veterinary Hematology Analyzer. The results showed that the mean total of erythrocytes was 6.54x106?l, and the mean hemoglobin level was 12.2 g / dL. Total erythrocytes and hemoglobin levels of Balinese cattle with organic forage were still in the normal range